The Earthscan reader on gender and forests - Colfer, C.J.P.; Elias, Marlène; Sijapati Basnett, Bimbika; Hummel, S.S. (Routledge, 2017)
There is currently much interest in mainstreaming gender in natural resource management, including forestry. This reader provides a collection of key articles on gender and forests published over the last 30 years. Including an editorial introduction and overview, it provides an accessible collection of excellent forestry-relevant social science within an overarching analytical framework and demonstrates the leading debates in the field. The book will be of great value to both biophysical science and social science students and to professionals in training. It focuses on people and forest interactions, providing a range of studies from both developed and developing countries. It includes theoretical analyses, methodological pieces, case studies, and cross-country comparisons, and it forms a companion volume to Gender and Forests: Climate Change, Tenure, Value Chains and Emerging Issues (2016).